Decision Analysis of Giving Credit Using Pairwise Comparisons and Scoring Methods (Case Study: Bank XYZ) - Priangga, Prima; Suryani, Erma (IPTEK The Journal for Technology and Science, 2019)
Kredit Usaha Rakyat (KUR) is a type of credit was given by Bank for segmen business Micro, Small and Medium Enterprises (UMKMK). Along with the high interest of the community in applying for credit to the Bank, it raises its own problems, namely determining the feasibility of customers. Determining this feasibility is important considering that KUR is one of the Government's programs in empowering the UMKMK industry sector, so that the risk of non-performing loans is expected to be minimized. The method used in this study is the Pairwise Comparisons and Scoring, based on the consideration that Pairwise Comparisons and Scoring are aids in priority of criteria, priority of sub criteria and giving scoring to determine lending decisions. Pairwise Comparisons are the basic concepts of the Analytical Hierarchy Process which have been proven to solve decision problems which involve many complex criteria. The results obtained in this study are priority of criteria, priority of sub criteria and scoring of debtors for the determination of debtors who are eligible or not eligible for receive credit. 30 debtors who were sampled in this study, 17 debtors were eligible to receive credit and 13 debtors were not eligible to receive credit.